EVALUATION OF TEMPERATURE DISTRIBUTION AND FLUID FLOW IN FUSION WELDING PROCESSES (Journal of Engineering, 2007)
A theoretical study of heat transfer and fluid flow phenomena in welding process has been carried out in the present work. The study involved the numerical solution of the transient NavierStokes and Energy equations of the weld pool region by using Finite Difference Method. The electromagnetic force field and buoyancy were included in the formulation The stream-vorticity formulation was used in the mathematical model. The numerical solution is capable of calculating the vorticity, stream function, velocity, temperature, and the interface movement of the weld pool in Gas Metal Arc Welding (GMAW). The model can be used to solve the Gas Tungesten Arc Welding (GTAW) problem. A numerical calculations algorithm was developed to carry out the numerical solution. The numerical results showed that the finger penetration phenomena occurs in the Gas Metal Arc weld is adequately explained through the application of the model. It is found that the frequency of spray transfer is a dominant factor in addition to shape of the weld pool geometry. A verification of numerical results was made through a comparison with a previous work, the agreement was good, confirming the capability and reliability of the proposed numerical algorithm in calculating fluid flow and heat transfer in Gas Metal Arc weld pools.